2011
DOI: 10.1002/pd.2726
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and natural history of fetuses presenting with pleural effusion

Abstract: Objective To describe the natural history of fetuses presenting with pleural effusion.Methods Between January 2005 and December 2009 all fetuses diagnosed with pleural effusion were followed up. Fetuses were divided into three groups: I, isolated pleural effusion; II, associated structural anomalies but normal karyotype; and III, chromosomal anomalies. Univariate and multivariate analyses were performed to determine the association between prenatal ultrasound findings and perinatal death.Results Fifty-six fetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 10 publications
2
22
0
11
Order By: Relevance
“…Even though survival rates for prenatal intervention (50%) and conservative management (52%) were similar in our cohort, those surviving after fetal therapy would likely not have survived if management had been conservative [15,16,21]. The 13 survivors from our conservative group predominantly had only mild or moderate-sized, unilateral effusions at presentation, which did not demonstrate clinical progression at follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Even though survival rates for prenatal intervention (50%) and conservative management (52%) were similar in our cohort, those surviving after fetal therapy would likely not have survived if management had been conservative [15,16,21]. The 13 survivors from our conservative group predominantly had only mild or moderate-sized, unilateral effusions at presentation, which did not demonstrate clinical progression at follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…This underlines the importance of a thorough ultrasound evaluation of the fetus as these malformations can influence both intrauterine survival as well as long-term outcome and have been associated with higher mortality [2] . The number of fetal aneuploidies of 18% in our study is also consistent with previous studies reporting 4.5-41.1% aneuploidies [2-5, 9, 19] and promotes fetal karyotyping in prenatally diagnosed hydrothorax [4,20] .…”
Section: Discussionmentioning
confidence: 99%
“…54 Bilateral hydrothorax is more often associated with fetal hydrops (71.4%), compared to unilateral hydrothorax (14.3%). 54 If we exclude the associated pathologies described by Ruano et al, the negative prognostic factors are: low gesta tional age at which the diagnosis was performed and at which the baby was delivered, the occurrence of hydrops and a bilateral form of hydrothorax. 51 A review of the literature showed that after multivariate analysis, hydrops remained the only negative prognostic factor.…”
Section: Bilateral Lung Hypoplasia With Hydrothoraxmentioning
confidence: 95%
“…5153 In 72.3 to 81% of cases, the hydrothorax is bilateral and, in 84% of cases, it is diagnosed in the third trimester of pregnancy. 51,54 Compared to the unilateral hydro thorax, the bilateral one is more often associated with malformations (21% vs 78.9%) or chromosomal abnor malities (17.4% vs 82.6%). 54 Bilateral hydrothorax is more often associated with fetal hydrops (71.4%), compared to unilateral hydrothorax (14.3%).…”
Section: Bilateral Lung Hypoplasia With Hydrothoraxmentioning
confidence: 98%
See 1 more Smart Citation